Self healing of metal composite interface - Shanmugam Logesh (2016)
Studies on self-healing material have gained an importance in many applications which reduce the maintenance cost and reusability of the product. The application extends to all fields from automotive to aerospace. Fibre metal laminate is a hybrid material used nowadays due to its structural integrity which is a combination of metal and composite. Often, there is a delamination between metal and composite interface if the bonding behaviour is weak. However, introducing a polymer interleaf will increase the bonding strength between metal and composite interface. This thesis presents an investigation of selfhealing and toughening performance of co-polymer (EMAA-polyethylene-co-meth acrylic acid) between composite adherend and metal composite interface (MCI). Furthermore, redux335k, which is a structural adhesive, used as a benchmark for both composite and metal composite specimens in this study. Carbon fibre composites were fabricated from unidirectional pre-preg with thin film of adhesive placed between composite plies and metal composite interface. Results from the double-cantilever-beam test showed that the incorporation of mendable thin film polymers improves interlaminar fracture toughness. This toughness gradually decreases upon further healing of material for three different cycles with the same procedures being followed. Recovery of self-healing material is about 72% for the first heal, 40 % for the second heal and 30% for the third heal. Moreover, the fracture toughness of the self-healing material is higher than redux335k for both monolithic composite specimen and hybrid specimen. Several methods are detailed to discuss the degradation of self-healing between MCI. Comparison of redux335k and self-healing copolymer EMAA is also shown in this thesis.